Controlled synthesis of ultrathin lanthanide oxide nanosheets and their promising pH-controlled anticancer drug delivery - Zhang, Xinyu (2015)
Various lanthanide oxides (Sm2O3 and Gd2O3) nanostructures were synthesized by a facile hydrothermal method. The loss of surfactants on the nanocrystals surface, followed by the resultant assembly is responsible for the formation of ultrathin nanosheets. Owing to strong surface effects, the different morphologies of the Sm2O3:5 % Eu and Gd2O3:5 % Eu nanocrystals present unique photoluminescence properties. As a proof-of-concept application, the as-obtained Sm2O3 and Gd2O3 ultrathin nanosheets exhibit promising pH-controlled anticancer drug-delivery behavior.